Convex-hull of Users under Adaptive Beam in WAN to Minimize Interference - Gautam, Bishal; Jani, Md. Rafsan; Ahammad, Bulbul; Rubaiat, Rahmina; Islam, Md. Imdadul (International Journal of Computer Sciences and Engineering, 2020)
In a mobile cellular network, users are located at a random position inside the cell. Sometimes users are highly concentrated in a region for example vicinity of a growth center on a holiday or near a stadium when a big football match is going on. In this case, a group of users under a convex hull can be covered by the beam of the adaptive Array Antenna System (AAS). Therefore the desired signal will be directional hence very low interference caused by the side lobes to other users. In this paper, an algorithm in the formation of a quick convex hull of a user group, determination of the inscribed angle of the convex hull from the center of the cell/Node-B, and formation of an adaptive beam to cover the convex hull. The paper reveals the results integrating the above three phenomena to achieve the communication of WAN (wide area network) with minimum interference. The concept of the paper is applicable in massive MIMO (multiple input and multiple output) of the 5G mobile cellular network.